1975
DOI: 10.1159/000136944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of &Delta;<sup>9</sup>-Tetrahydrocannabinol and Cannabinol in Man

Abstract: The interaction of Δ9-tetrahydrocannabinol (Δ9-THC) and cannabinol (CBN) was studied in man. Five male volunteers were given placebo, 50 mg CBN, 25 mg Δ9-THC, 12.5 mg Δ9-THC + 25 mg CBN, and 25 mg Δ9-THC + 50 mg CBN (orally). Administrations were spaced 1 week apart. With physiological measures, Δ9-THC produced an increase in heart rate while CBN did not. When combined, no change of the Δ9-THC effect occurred. No changes occurred on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…Thermoregulation is a critical component of homeostasis and is critical for survival across endothermic and ectothermic species. Beyond self-reported coldness (Hollister, 1971) cannabinoids do not induce the overt, statistically significant hypothermia in humans (Karniol et al, 1975; Fant et al, 1998) that is observed in rodents. However, the present study reveals that MAGL protects mice from thermal dysregulation caused by LPS or cold ambient temperature.…”
Section: Discussionmentioning
confidence: 95%
“…Thermoregulation is a critical component of homeostasis and is critical for survival across endothermic and ectothermic species. Beyond self-reported coldness (Hollister, 1971) cannabinoids do not induce the overt, statistically significant hypothermia in humans (Karniol et al, 1975; Fant et al, 1998) that is observed in rodents. However, the present study reveals that MAGL protects mice from thermal dysregulation caused by LPS or cold ambient temperature.…”
Section: Discussionmentioning
confidence: 95%
“…For example, cannabinol (at a concentration of 0.30%) was one constituent of the marijuana used in these studies. Although cannabinol does not have THClike effects itself (Hollister 1973;Perez-Reyes et al 1973), it has been shown to enhance subjects' reports of feeling drugged, drunk, dizzy, and drowsy in response to THC (Karniol et al 1975;Musty et al 1976). Thus, it would be of interest systematically to vary the concentrations of cannabinol and other cannabinoids to determine whether they contribute to the effects of marijuana.…”
Section: Discussionmentioning
confidence: 99%
“…In attempting to quantify the dose of Δ-9-THC extracted from a typical cannabis cigarette, several factors need to be considered including, but not limited to, the weight of a cannabis cigarette, the potency of Δ-9-THC in the herbal cannabis preparation, and the presence of other cannabinoids (Karniol and Carlini 1973;Karniol et al 1974Karniol et al , 1975Turner et al 1980). Furthermore, the amount of Δ-9-THC delivered is influenced by several factors including the rate of inhalation, depth of puffs, duration of puffs, volume inhaled, extent of breath-holding after inhalation, the amount lost by smoke escaping into the air or respiratory dead space, vital capacity, the length of cigarette smoked, the adeptness of smoking, and the subject's overall experience in titrating the dose.…”
Section: Route Of Administrationmentioning
confidence: 99%